2020
DOI: 10.1101/2020.06.10.143693
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome modularization reveals overlapped gene topology is necessary for efficient viral reproduction

Abstract: Sequence overlap between two genes is common across all genomes, with viruses having high proportions of these gene overlaps. The biological function and fitness effects of gene overlaps are not fully understood, and their effects on gene cluster and genome-level refactoring are unknown.The bacteriophage φX174 genome has ~26% of nucleotides involved in encoding more than one gene. In this study we use an engineered φX174 phage containing a genome with all gene overlaps removed, to show that gene overlap is cri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 118 publications
(126 reference statements)
0
6
0
Order By: Relevance
“…While coding potential was retained (Fig. 5a ), this refactoring led to numerous phenotypic defects, including a substantial reduction in burst size and lower attachment efficiency, along with large changes in levels of several essential assembly and replication proteins produced during the infection cycle 139 .
Fig.
…”
Section: Overlapping Genes In Bioengineeringmentioning
confidence: 99%
“…While coding potential was retained (Fig. 5a ), this refactoring led to numerous phenotypic defects, including a substantial reduction in burst size and lower attachment efficiency, along with large changes in levels of several essential assembly and replication proteins produced during the infection cycle 139 .
Fig.
…”
Section: Overlapping Genes In Bioengineeringmentioning
confidence: 99%
“…Phage genomes are typically small and highly gene dense, which is likely to limit the overall complexity of their native gene expression programs [33,34]. The phage PhiX, for instance, encodes only 11 essential genes on a genome that spans ≈5,000 base-pairs [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Our study is motivated by the observation that naturally evolved phages appear to regulate their gene expression via the mechanisms discussed here. Phage genomes are typically small and highly gene dense, which is likely to limit the overall complexity of their native gene expression programs [31][32][33][34]. Even with relatively small genomes, numerous studies have shown that phages are capable of producing complex gene expression dynamics over the course of an infection cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Such regions have important biological and evolutionary implications. First, they are associated with virus within-host multiplication, betweenhost transmission, disease severity and strength of host immune response [3][4][5][6]. Second, viruses are subjected to strong selection for maintaining smaller genomes because this (i) reduces the chances for deleterious mutations to become fixed in the virus genome, particularly in viruses with high mutation rates; (ii) improves virus fitness due to faster replication; and (iii) optimizes virion formation due to physical limitations imposed by the capsid size [7][8][9].…”
Section: Introductionmentioning
confidence: 99%